Capturing extracellular matrix properties in vitro: Microengineering materials to decipher cell and tissue level processes. Issue 9 (May 2016) - Abdeen, Amr A; Lee, Junmin; Kilian, Kristopher A
Rapid advances in biology have led to the establishment of new fields with tremendous translational potential including regenerative medicine and immunoengineering. One commonality to these fields is the need to extract cells for manipulation in vitro; however, results obtained in laboratory cell culture will often differ widely from observations made in vivo. To more closely emulate native cell biology in the laboratory, designer engineered environments have proved a successful methodology to decipher the properties of the extracellular matrix that govern cellular decision making. Here, we present an overview of matrix properties that affect cell behavior, strategies for recapitulating important parameters in vitro, and examples of how these properties can affect cell and tissue level processes, with emphasis on leveraging these tools for immunoengineering.